Effect of avocado/soybean unsaponifiables (ASU) on osseointegration in rats with experimental arthritis - de Paula, Luiz Guilherme Freitas; de Oliveira, Guilherme José Pimentel Lopes [UNESP]; Pinotti, Felipe Eduardo [UNESP]; Grecchi, Bruna Biagioni [UNESP]; de Aquino, Sabrina Garcia; Marcantonio, Rosemary Adriana Chiérici [UNESP] (Quintessence Publishing, 2018)
Purpose: To evaluate the influence of the use of avocado/soybean unsaponifiables (ASU) on osseointegration of implants in animals with experimental arthritis. Materials and Methods: One hundred twenty rats were randomly divided into four groups: CTR, healthy animals and saline solution administration; ASU, healthy animals and ASU administration; ART, arthritic animals and saline solution administration; and ART/ASU, arthritic animals and ASU administration. The solutions were administered daily by gavage, beginning 7 days before the surgical procedures until the completion of the experimental period (15, 30, and 60 days after the placement of the implants in the tibia). The osseointegration of the implants was evaluated by histometric analysis (bone-to-implant contact [% BIC], bone area between the threads [% BBT]) and biomechanical analysis. Microcomputed tomography (micro-CT) analysis was used to assess bone volume in the vicinity of the implant. Immunohistochemistry analysis was performed to assess the expression of osteocalcin and transforming growth factor beta 1 (TGF-β1). Results: The ART/ASU group showed a decreased percentage of bone in the area around the implant compared with the ASU and ART groups (15 and 30 days). The ART/ASU group showed increased removal torque values (30 days) and % BIC and % BBT (30 to 60 days) compared with the ART group. The ASU group had increased % BIC values compared with the ART and CTR groups (60 days). The CTR group had the highest expression of osteocalcin, while the ASU group presented the highest expression of TGF-β1 at 60 days. Conclusion: The ASU administration improved the osseointegration, particularly in animals with induced arthritis.
Keywords: Bone remodeling; Herbal medicine; Osseointegration; Phytotherapy; Rheumatoid arthritis